Dari Masa Kolonial Hingga Revolusi Fisik: Jejak Eksistensi Pangkalan Udara Militer Panasan Surakarta (1940-1949) - Dadan Adi Kurniawan (Universitas Negeri Gorontalo, 2019)
The air military is an important part of supporting the strength and sovereignty of a country. In gathering strength, the air military generally has a center (headquarters) that is in a